INTERAKSI SOSIAL ANAK KORBAN EKSPLOITASI DI KAWASAN RUMBAI - Eljani Simanjuntak; Tri Umari; Roby Maiva Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research designed to describe child victims of exploitationaround Rumbai and to describe social interaction of child victims of exploitation.Subject of this research is five children victims of exploitation as scavenger age nine upto fourteen years old. This research is using qualitative research methods. The datacollection technique is observations and interviews. This research using data analysistechnique of Miles and Huberman. Result of this research show child victims ofexploitation around Rumbai is elementary school’s student, age nine up to fourteenyears old, scavenging as long as 1-3 years, scavenging with their family and friends,about six up to nine hours in a day. They are using long shirt and hat, but not usegloves. When they are scavenging, the kind of social interaction around Rumbai iscooperation, competition, accommodation, and conflict.Key Words: Profile, Social Interaction, Child Victims Of Exploitation